2001
DOI: 10.1149/1.1373657
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Properties of LiCoO[sub 2]-Coated LiMn[sub 2]O[sub 4] Prepared by Solution-Based Chemical Process

Abstract: In order to enhance both the cycle stability at elevated temperatures and the rate capability of LiMn2O4, the surface of LiMn2O4 was covered with fine LiCoO2 particles prepared by a solution-based chemical process. The amount of LiCoO2 measured with inductively coupled plasma was about 7 mol %. LiCoO2 -coated LiMn2O4 had an excellent cycle stability at 65°C compared to pure LiMn2O4. This can be explained by suppression of the Mn dissolution. The rate capability of LiCoO2 -coated LiMn2O4 improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Choi [5] reported that LiNi 1/3 Co 1/3 Mn 1/3 O 2 gave a capacity of about 184 mAh g −1 over 2.5-4.6 V. However, its capacity fading became faster than that over 2.5-4.4 V. Surface coating was proven to be an effective method to reduce the electrolyte decomposition on the surface of the cathode materials. Experiments such as surface coating of LiMn 2 O 4 with MgO [6], Al 2 O 3 [6], SiO 2 [7], and LiCoO 2 [6,8,9] and surface coating of 5-V materials LiNi 0.5 Mn 1.5 O 4 with ZnO [10] were reported to improve markedly the capacity retention at elevated temperatures. Studies on the surface modifying of LiCoO 2 [11], LiNiO 2 [12], and LiNi 0.8 Co 0.2 O 2 [13,14] were also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Choi [5] reported that LiNi 1/3 Co 1/3 Mn 1/3 O 2 gave a capacity of about 184 mAh g −1 over 2.5-4.6 V. However, its capacity fading became faster than that over 2.5-4.4 V. Surface coating was proven to be an effective method to reduce the electrolyte decomposition on the surface of the cathode materials. Experiments such as surface coating of LiMn 2 O 4 with MgO [6], Al 2 O 3 [6], SiO 2 [7], and LiCoO 2 [6,8,9] and surface coating of 5-V materials LiNi 0.5 Mn 1.5 O 4 with ZnO [10] were reported to improve markedly the capacity retention at elevated temperatures. Studies on the surface modifying of LiCoO 2 [11], LiNiO 2 [12], and LiNi 0.8 Co 0.2 O 2 [13,14] were also reported.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome the challenges posed by dendritic growth in pure lithium metal cathodes, the battery community resorted to layered-structured frameworks of lithium compounds such as transitional metal oxides 5,6 , spinels 7,8 and phospho-olivines 9,10 as cathode materials for rechargeable lithium batteries. In 1980, Goodenough and co-workers 11 first demonstrated the use of LiCoO 2 as cathodes with a theoretical capacity of B273 mAh g À 1 and a theoretical energy density of 1.11 kWh kg À 1 .…”
mentioning
confidence: 99%
“…The reason for the improved elevated temperature properties of LMO coated by other electrode materials is that the surface coating reduces the dissolution of Mn, which results from the suppression of the electrolyte decomposition. The coated electrode materials include LiCoO 2 performed by sol-gel methods [32][33][34] [39], and LiCu x Mn 2−x O 4 [40]. The synthesis methods and the electrochemical performance of coating by other electrode materials are plotted in Table 2.…”
Section: Electrode Materialsmentioning
confidence: 99%